2011
DOI: 10.2174/1875414701104010001
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity of Some Botanical Extracts, Commercial Insecticides and their Binary Mixtures Against the Housefly, Musca Domestica L.

Abstract: Following preliminary screening of 13 ethanolic plant extracts, belonging to 10 different families, a total of 11 extracts were subjected to detailed toxicity evaluation against the larval stage of the housefly, Musca domestica L. The larvicidal LC 50 values were < 100 ppm for Piper nigrum (50.1 ppm), Azadirachta indica (76.9 ppm), Conyza aegyptiaca (77.0 ppm) and Cichorium intybus (96.8 ppm); representing the highest potent extracts among the bioassayed candidates. Punica granatum extract exhibited the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…In addition to its antibacterial activities, it also shows antiviral, antiprotozoan and anti-fungal actions. Their anti-fungal actions are getting more importance as these compounds are now being incorporated in to fungicide preparations which are cost effective as well as environmental friendly (Afzal et al, 2010) and also as fly repellent (Mansour et al, 2011). Figure 1 Beneficial effects of probiotics, prebiotics, vitamins, antimicrobial peptides and herbs as growth promoters in poultry.…”
Section: Antimicrobials Of Plant Origin / Phytobioticsmentioning
confidence: 99%
“…In addition to its antibacterial activities, it also shows antiviral, antiprotozoan and anti-fungal actions. Their anti-fungal actions are getting more importance as these compounds are now being incorporated in to fungicide preparations which are cost effective as well as environmental friendly (Afzal et al, 2010) and also as fly repellent (Mansour et al, 2011). Figure 1 Beneficial effects of probiotics, prebiotics, vitamins, antimicrobial peptides and herbs as growth promoters in poultry.…”
Section: Antimicrobials Of Plant Origin / Phytobioticsmentioning
confidence: 99%
“…Plates 1 and 2 showed that distinct malformations of larvae and pupae of the house fly were induced after treatment of the third larval instar with LC50 and LC75 of peppermint and lavender. Morphological larvae abnormalities ( Khater and Shalaby (2008), Khater and Khater (2009) and Mansour et al (2011), respectively. The abnormalities could be attributed to the metamorphosis inhibiting effect of the essential oils, as a result of the disturbance of hormonal control.…”
Section: Morphologic Abnormalitiesmentioning
confidence: 99%
“…In a previous studies using imidacloprid, as Larvicidal activity was observed in the direct surrounding of treated animals [67,68]. Arther et al concluded that monthly imidacloprid application of 7.5 to 10 mg/kg will rapidly kill existing and reinvesting flea infestation in dog and break the flea life cycle by killing adult fleas before egg production begins [69][70][71][72][73][74].…”
Section: Compoundsmentioning
confidence: 99%